MR Imaging Characteristics Associate with Tumor-Associated Macrophages in Glioblastoma and Provide an Improved Signature for Survival Prognostication - Zhou, J.; Reddy, M.V.; Wilson, B.K.J.; Blair, D.A.; Taha, A.; Frampton, C.M.; Eiholzer, R.A.; Gan, P.Y.C.; Ziad, F.; Thotathil, Z.; Kirs, S.; Hung, N.A.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: In glioblastoma, tumor-associated macrophages have tumor-promoting properties. This study determined whether routine MR imaging features could predict molecular subtypes of glioblastoma that differ in the content of tumor-associated macrophages.MATERIALS AND METHODS: Seven internally derived MR imaging features were assessed in 180 patients, and 25 features from the Visually AcceSAble Rembrandt Images feature set were assessed in 164 patients. Glioblastomas were divided into subtypes based on the telomere maintenance mechanism: alternative lengthening of telomeres positive (ALT+) and negative (ALT−) and the content of tumor-associated macrophages (with [M+] or without [M−] a high content of macrophages). The 3 most frequent subtypes (ALT+/M−, ALT−/M+, and ALT−/M−) were correlated with MR imaging features and clinical parameters. The fourth group (ALT+/M+) did not have enough cases for correlation with MR imaging features.RESULTS: Tumors with a regular margin and those lacking a fungating margin, an expansive T1/FLAIR ratio, and reduced ependymal extension were more frequent in the subgroup of ALT+/M− (P < .05). Radiologic necrosis, lack of cystic component (by both criteria), and extensive peritumoral edema were more frequent in ALT−/M+ tumors (P < .05). Multivariate testing with a Cox regression analysis found the cystic imaging feature was additive to tumor subtype, and O6-methylguanine methyltransferase (MGMT) status to predict improved patient survival (P < .05).CONCLUSIONS: Glioblastomas with tumor-associated macrophages are associated with routine MR imaging features consistent with these tumors being more aggressive. Inclusion of cystic change with molecular subtypes and MGMT status provided a better estimate of survival.ALTalternative lengthening of telomeresALT−alternative lengthening of telomeres negativeALT+alternative lengthening of telomeres positiveIDHisocitrate dehydrogenaseM+a tumor with a high content of tumor-associated macrophagesM−a tumor with a low content of tumor-associated macrophagesMGMTO6-methylguanine methyltransferasePTEperitumoral edemaVASARIVisually AcceSAble Rembrandt Images